The Corona Virus and Labor Rights Issues: How Do Workers Get Their Rights? - Mardiansyah, Diki (The Indonesian Journal of International Clinical Legal Education, 2020)
The impact of Covid-19 is very broad and comprehensive in all human life. Students must learn from home, workers work from home, and all people worship from home. Really, a life that I never imagined before. Students complain about online lectures because assignments are increasing, internet quota runs out quickly, not to mention students from remote areas that are difficult to signal. This is clearly very troublesome for them. Even for workers who cannot work from home, the appeal to work from home is not valid. They are not office workers or lecturers who can work from home. They have to work on the streets, in the field, even in the fields or gardens. It is impossible for farmers to work from home. This can make us realize that we cannot eat money. Food needs will still be fulfilled by farmers. Referring to the right to decent work and livelihood, it is fitting for the Government to ensure that there is no Termination of Employment by the company and the provision of adequate wages in accordance with the provisions of the legislation in force. This paper will discuss the impact events of Covid-19 that have an impact on workers, especially workers. Not a few workers in various regions in Indonesia were laid off and laid off as a result of the Corona pandemic.